Spatial Analysis of Population Pressure and Agricultural Land Carrying Capacity in Slawi District, Tegal Regency - Fandi Maulana Akhmad; M. Fikri Amrullah (Jambura Geoscience Review, 2026)
Population growth and rising demand for housing have accelerated agricultural land conversion in the Slawi District, Tegal Regency, raising concerns about the capacity of available land to support the local population. This study aimed to analyze the spatial patterns of population pressure and the carrying capacity of agricultural land at the village level in the Slawi District. A quantitative approach was employed using the Soemarwoto (1985) Model II framework to calculate the population pressure index (TP) and agricultural land carrying capacity (DDLP). Secondary data were obtained from the Agriculture, Fisheries, and Forestry Extension Center, the Food Security and Agriculture Service, and the Central Bureau of Statistics. The data were quantitatively processed and spatially mapped using GIS to identify variations among villages. The results show that the Slawi District experiences high population pressure, indicated by a TP value of 1.21 people/ha, while its agricultural land carrying capacity is classified as low, with a DDLP value of 0.83. At the village level, areas with higher population pressure generally show lower agricultural land carrying capacity, indicating an inverse relationship between the two indicators. These findings demonstrate that the distribution of land resource capacity in the Slawi District is spatially uneven, and that several villages are under greater pressure than others. The study concludes that strengthening land-use control and protecting sustainable agricultural land are important to reduce the risk of continued land conversion and declining land support capacity.